Chlorophyll Content of Chlorella vulgaris (Beijerinck, 1890) on Different Light Intensity - Khairunnisa, Khairunnisa; Hartati, Retno; Widowati, Ita (Buletin Oseanografi Marina, 2024)
Chlorella vulgaris is a green microalga (Chlorophyta) known to produce chlorophyll pigment as its primary pigment. Chlorophyll is known for its health benefits because it helps heal wounds and prevent hemophilia and diabetes and asthma. Chlorophyll is one of the pigments targeted as a functional food source. One of the environmental parameters that can affect chlorophyll content is the presence of light. This study aims to determine the effect of differences in light intensity on the chlorophyll content of C. vulgaris. The method used in this research is experimental, conducted in the laboratory using a completely randomized design (RAL). ANOVA is the statistical analysis used to analyze the effect of light intensity on chlorophyll content in C. vulgaris. C. vulgaris was cultivated with three different light intensity treatments, namely 1500, 3000, and 4500 lux, with three repetitions each. The growth of C. vulgaris was observed for 8 x 24 hours and then harvested by centrifugation on the eighth day to obtain the wet biomass. Cultivation wet biomass was extracted using acetone PA solvent. The acetone extract of C. vulgaris was analyzed for its chlorophyll pigment content using a spectrophotometer at 645 and 663 nm absorbance. The highest content of chlorophyll-a, b, and chlorophyll produced at a light intensity of 1500 lux was 26.2, 48.5, and 74.7 µg/ml, respectively. According to the results of statistical analysis, it can be concluded that different light-intensity treatments did not show a significant effect (p>0.05) on the content of chlorophyll-a, b, and total chlorophyll in C. vulgaris.